The early development of executive function and its relation to social interaction: a brief review - Moriguchi, Yusuke (Frontiers in Psychology, 2014)
Executive function (EF) refers to the ability to execute appropriate actions and to inhibit inappropriate actions for the attainment of a specific goal. Research has shown that this ability develops rapidly during the preschool years. Recently, it has been proposed that research on executive function should consider the importance of social interaction. In this article, recent evidence regarding the early development of executive function and its relation to social interaction has been reviewed. Research consistently showed that social interaction can influence executive function skills in young children. However, the development of executive function may facilitate the cognitive skills that are important for social interaction. Taken together, there might be functional dependency between the development of executive function and social interaction.